2024
DOI: 10.1111/jipb.13626
|View full text |Cite
|
Sign up to set email alerts
|

An alfalfa MYB‐like transcriptional factor MsMYBH positively regulates alfalfa seedling drought resistance and undergoes MsWAV3‐mediated degradation

Kun Shi,
Jia Liu,
Huan Liang
et al.

Abstract: Drought is a major threat to alfalfa (Medicago sativa L.) production. The discovery of important alfalfa genes regulating drought response will facilitate breeding for drought‐resistant alfalfa cultivars. Here, we report a genome‐wide association study of drought resistance in alfalfa. We identified and functionally characterized an MYB‐like transcription factor gene (MsMYBH), which increases the drought resistance in alfalfa. Compared with the wild‐types, the biomass and forage quality were enhanced in MsMYBH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Many studies have shown that transcription factors such as bHLH, NAC, WRKY, MYB, and HSP play important roles under abiotic stress. Compared with those of wild-type alfalfa, the drought resistance of MsMYBoverexpressing plants increased, and the biomass and quality of the plant improved (Shi et al, 2024). Overexpression of SlbHLH96 in tomato improves drought resistance by stimulating the expression of genes encoding antioxidants, ABA signaling molecules, and stress-related proteins (Liang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that transcription factors such as bHLH, NAC, WRKY, MYB, and HSP play important roles under abiotic stress. Compared with those of wild-type alfalfa, the drought resistance of MsMYBoverexpressing plants increased, and the biomass and quality of the plant improved (Shi et al, 2024). Overexpression of SlbHLH96 in tomato improves drought resistance by stimulating the expression of genes encoding antioxidants, ABA signaling molecules, and stress-related proteins (Liang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%